Perception of feeling safe perioperatively: a concept analysis - Fanny Larsson; Ulrica Strömbäck; Silje Rysst Gustafsson; Åsa Engström (International Journal of Qualitative Studies on Health & Well-Being, 2023)
Purpose The purpose of this study was to explore the concept of feeling safe, from the patient perspective, in a perioperative context. Method The eight-step concept analysis approach proposed by Walker and Avant was utilized to examine the attributes of feeling safe. Uses of the concept, defining attributes as well as antecedents, consequences and empirical referents are presented to describe the concept. Case examples are provided in order to assist the understanding of the defining attributes. Results Feeling safe is defined as: a person that does not feel worried or threatened. Three attributes were identified: Participation, Control and Presence. Knowledge and Relationship are the antecedents of feeling safe, while Feeling Acknowledged and Trust are the consequences. Empirical referents are explored in order to find a way to measuring the perceived feeling of safety. Conclusion This concept analysis underscores the importance of including patients’ perceptions in traditional patient safety work. Patients who feel safe perceive that they participate in their care, that they are in control, and that they feel the presence of both healthcare staff and relatives. The perceived feeling of security could, by extension, promote the postoperative recovery of patients undergoing surgery by positively affect the process of recovery.